Characterization and biological activities of essential oils from piper spp. - Logihad, Rosilin (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study was performed to identify the chemical composition of essential oils extracted from root, stem and leaves of the three Piper spp. which are Piper sp1, P. betle and P. sarmentosum. The essential oils was extracted by using hydrodistillation and then subjected to gas chromatography-flame ionization detector for analysis purpose and Kovat indices calculation. The percentage yield of essential oil from the root, stem and leaves were generally ranged from 0.3% - 2.47% (v/w) and the result showed that P. sarmentosum give the highest percentage yield of essential oil. For overall, there are 102 components detected from the root part of Piper spp., 98 components from stem part and 75 components from leaves part. These components include the 25 terpenes compound, 46 ester, 57 aldehyde and ketone, 47 alcohol, 4 acids and 39 others. The close relationships between these species were analyzed by using Hierarchical Cluster Analysis and the dendogram produced showed the similarities in term of chemical composition from Piper spp. Toxicity test showed that P. sarmentosum was the most toxic substance for root part with LC50 of 55.06 µg/mL. While, for the both of stem and leaves part, Piper sp1 showed the most toxic potential towards the larvae with LC50 of 66.24 µg/mL and 56.55 µg/mL respectively. Antitermite activity of the Piper spp. showed that P. sarmentosum was the most toxic against the termites for all parts.